2022
DOI: 10.3390/ijms23137011
|View full text |Cite
|
Sign up to set email alerts
|

KSK-74: Dual Histamine H3 and Sigma-2 Receptor Ligand with Anti-Obesity Potential

Abstract: Many studies involving compounds that enhance histamine release, such as histamine H3 receptor (H3R) antagonists, have shown efficacy in inhibiting weight gain, but none have passed clinical trials. As part of the search for H3 receptor ligands that have additional properties, the aim of this study is to evaluate the activity in the reduction in weight gain in a rat model of excessive eating, as well as the impact on selected metabolic parameters, and the number and size of adipocytes of two new H3R antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
5
0
2
Order By: Relevance
“…In our previous studies on the effect of tested ligands on body weight in a model of excessive eating in rats, we showed that spontaneous activity—measured by long-term motility monitoring in home cage conditions—is not significantly affected by any of these ligands when administered once and chronically i.p. at a dose of 10 mg/kg/day [ 21 , 22 , 23 , 24 ]. Additional studies are required to indicate the exact mechanism underlying this effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous studies on the effect of tested ligands on body weight in a model of excessive eating in rats, we showed that spontaneous activity—measured by long-term motility monitoring in home cage conditions—is not significantly affected by any of these ligands when administered once and chronically i.p. at a dose of 10 mg/kg/day [ 21 , 22 , 23 , 24 ]. Additional studies are required to indicate the exact mechanism underlying this effect.…”
Section: Discussionmentioning
confidence: 99%
“…The study evaluating the activities of alanine aminotransferase (AlaT), aspartate aminotransferase (AspaT), gamma-glutamyl transpeptidases (gGT), and alkaline phosphatase (ALP) was carried out after completing the excessive eating model experiments described in our previous work [ 21 , 22 , 23 ]. Compounds were administered for twenty-eight days at a dose of 10 mg/kg b.w./day.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Хемореактомный анализ показал возможность того, что фонтурацетам -наиболее активный ингибитор H3R (IC50 = 55 нМ). Соединения, которые усиливают высвобождение гистамина (такие как селективные антагонисты H3R), исследуются как средства для лечения ожирения [43].…”
Section: хемореактомное исследование эффектов фонтурацетама: молекуля...unclassified